Uso de inteligencia artificial en el marketing empresarial: una revisión sistemática - Choque-Yarasca, Christel; Barrutia-Montoya, Nilda; Geraldo-Campos, Luis Alberto (LACCEI, 2025)
The objective is to identify the impact of artificial intelligence in business marketing, the main clusters, the AI tools that have been applied for the benefit of marketing, their implementation process, the strategies employed in the application and the main challenges of AI in marketing application. To this end, a systematic review was conducted following the PRISMA guidelines and the PICO question of the empirical studies found in the Scopus and Web of Science (WoS) databases. Subsequently, a bibliometric analysis was developed and a total of 35 scientific articles were identified in journals indexed between the years 2019 and 2024 that met the inclusion criteria and were ready to extract the information. It was identified that the application of AI in companies improved the quality of predictions about customer behavior, which helps to perform better segmentation and personalization of offers to the target audience, and to increase customer retention. It was concluded that there is a close connection between artificial intelligence, marketing and commerce, and emphasis was placed on emerging areas such as data mining, machine learning, ChatGPT-4, neural networks, BiLSTM, chatbots algorithms and virtual assistants, which are revolutionizing the field.